A genome-wide association meta-analysis on lipoprotein (a) concentrations adjusted for apolipoprotein (a) isoforms - Mack, Salome; Coassin, Stefan; Rueedi, Rico; Yousri, Noha A; Seppälä, Ilkka; Gieger, Christian; Schönherr, Sebastian; Forer, Lukas; Erhart, Gertraud; Marques-Vidal, Pedro; Ried, Janina S; Waeber, Gerard; et al. (Journal of lipid research, 2017)
High lipoprotein (a) [Lp(a)] concentrations are an independent risk factor for cardiovascular outcomes. Concentrations are strongly influenced by apo(a) kringle IV repeat isoforms. We aimed to identify genetic loci associated with Lp(a) concentrations using data from five genome-wide association studies (n = 13,781). We identified 48 independent SNPs in the and 1 SNP in the gene region to be significantly associated with Lp(a) concentrations. We also adjusted for apo(a) isoforms to identify loci affecting Lp(a) levels independently from them, which resulted in 31 SNPs (30 in the , 1 in the gene region). Seven SNPs showed a genome-wide significant association with coronary artery disease (CAD) risk. A rare SNP (rs186696265; MAF ∼1%) showed the highest effect on Lp(a) and was also associated with increased risk of CAD (odds ratio = 1.73, = 3.35 × 10 ). Median Lp(a) values increased from 2.1 to 91.1 mg/dl with increasing number of Lp(a)-increasing alleles. We found the -determining allele of rs7412 to be significantly associated with Lp(a) concentrations ( = 3.47 × 10 ). Each allele decreased Lp(a) by 3.34 mg/dl corresponding to ∼15% of the population's mean values. Performing a gene-based test of association, including suspected Lp(a) receptors and regulators, resulted in one significant association of the gene with Lp(a) ( = 3.4 × 10 ). In summary, we identified a large number of independent SNPs in the gene region, as well as the allele, to be significantly associated with Lp(a) concentrations.